The Influence of the Covid-19 Pandemic on the Financial Performance of Construction SOEs Listed on the Indonesia Stock Exchange - Alvia Herna Tertia; Waspodo Tjipto Subroto (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of the Covid-19 Pandemic on the financial performance of BUMN companies in the construction sector listed on the Indonesia Stock Exchange for the 2016-2020 quarterly period and its development based on the assessment contained in the Decree of the Minister of State-Owned Enterprises Number: KEP-100 / MBU. / 2002. This study uses technical trend analysis. In this study, the population used is a state-owned company in the construction sector listed on the Indonesia Stock Exchange for the 2016-2020 quarterly period. There are four companies. The data collection technique used is documentation in the form of company financial reports for 2016-2020 and uses evaluation techniques based on the Decree of the Minister of State-Owned Enterprises Number: KEP-100 / MBU / 2002. The study results based on trend analysis indicate that the Covid-19 pandemic influences the financial performance of BUMN in the construction sector in the form of a decrease in the company's financial performance.